2015
DOI: 10.1017/s1041610215000629
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior and assisted suicide in dementia

Abstract: Although dementia might not confer a significant overall risk for suicidal behavior, clinicians still need to consider the potential for suicide in vulnerable individuals particularly early in the dementia course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 82 publications
8
68
0
1
Order By: Relevance
“…This could indicate that dementia was under‐diagnosed or under‐detected in this cohort of suicide deaths, as it is also estimated to be in the general population, although this is probably less likely in a nursing home setting. However, this finding is consistent with studies reporting low suicide risk among people with dementia, suggesting that dementia patients may be unable to formulate intent or implement the means to suicide due to their cognitive impairment . A large proportion of residents had at least 1 (86.5%) physical health diagnosis, often with multiple comorbidities and physical impairments.…”
Section: Discussionsupporting
confidence: 91%
“…This could indicate that dementia was under‐diagnosed or under‐detected in this cohort of suicide deaths, as it is also estimated to be in the general population, although this is probably less likely in a nursing home setting. However, this finding is consistent with studies reporting low suicide risk among people with dementia, suggesting that dementia patients may be unable to formulate intent or implement the means to suicide due to their cognitive impairment . A large proportion of residents had at least 1 (86.5%) physical health diagnosis, often with multiple comorbidities and physical impairments.…”
Section: Discussionsupporting
confidence: 91%
“…While people living with dementia may still have a lot of things to enjoy, research also shows that they may experience burdensome symptoms as the disease progresses. 9,10 Such thoughts may trigger formal requests for physician-assisted suicide or euthanasia, to be carried out either early in the disease trajectory (while still competent) or later when decisional capacity has been lost. [5][6][7] Others have found that anticipated experiences of patients living with dementia are often more negative than their actual experiences.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nonetheless, increased awareness of the challenges of living with dementia can result in some diagnosed people seriously contemplating a hastened death. 9,10 Such thoughts may trigger formal requests for physician-assisted suicide or euthanasia, to be carried out either early in the disease trajectory (while still competent) or later when decisional capacity has been lost. In The Netherlands, where the law on assisted death imposes no limit on life expectancy, physicians can provide assistance in dying at both the early and late stages of dementia, provided that the legal requirements are met.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of suicidal behaviour in dementia noted that the overall quality of studies examining self-harm was poor and from the available studies it was unclear if dementia increased the risk of self-harm (Draper, 2015). The hospitalisation rate for self-harm for individuals with dementia aged 60 years and older was double the rate for individuals without dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Prior anecdotal evidence suggested that individuals with dementia who self-harm also experience comorbid mental health conditions (Draper, 2015). Prior anecdotal evidence suggested that individuals with dementia who self-harm also experience comorbid mental health conditions (Draper, 2015).…”
Section: Discussionmentioning
confidence: 99%